Impact of Transformational Leadership on Employee Performance with the mediation impact of employee engagement - Raveendran, T. (Wayamba University of Sri Lanka, 2022)
The objective of the current study is to examine the mediating effect of Employee Engagement (EE) in the association between Transformational Leadership (TFL) and Employee Performance (EP). The study employed a cross sectional descriptive method and was based on 218 front line employees who were working at MOH Offices in the Jaffna District. Simple random sampling method was employed. Established questionnaires were used to measure the variables. Exploratory factor analysis was used to get the factor structure of each study construct. Subsequently regression analysis was performed to identify the association among the variables. The results revealed that TFL positively influences EP as well as EE. EE also positively influences EP. In addition, EE mediates the association between TFL and EP. The study highlights the importance of TFL in promoting performance among the health sector employees.
Keywords: Employee engagement; Work performance; Transformational leadership; Health sector